2017
DOI: 10.1111/cid.12552
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive treatments in bone grafts for implant‐based rehabilitation: Systematic review and meta‐analysis

Abstract: Bioactive proteins may improve bone formation in alveolar ridge augmentation, and reduce residual bone grafts in sinus floor augmentation. Further studies are needed to evaluate the long-term effect of using bioactive treatments for implant-based rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
(181 reference statements)
1
2
0
2
Order By: Relevance
“…In both cases, PMA and NMA (low quality of evidence) found no statistically significant difference. Such results are in agreement with those of previous studies 63,64,82,89,90 . Nevertheless, the application of MSCs in combination with any osteoconductive biomaterials (xenografts or autograft with xenografts) resulted in a greater amount of NBF when the healing time was more than 6 months, suggesting that remodelling may require a longer time when using these materials, in spite of the association with MSCs.…”
Section: Autogenous Bone Vs Bmp-2/different Bone Grafts Plus Mscssupporting
confidence: 94%
“…In both cases, PMA and NMA (low quality of evidence) found no statistically significant difference. Such results are in agreement with those of previous studies 63,64,82,89,90 . Nevertheless, the application of MSCs in combination with any osteoconductive biomaterials (xenografts or autograft with xenografts) resulted in a greater amount of NBF when the healing time was more than 6 months, suggesting that remodelling may require a longer time when using these materials, in spite of the association with MSCs.…”
Section: Autogenous Bone Vs Bmp-2/different Bone Grafts Plus Mscssupporting
confidence: 94%
“…In the meta-analysis on the treatment of furcation defects, the estimate of the first trial was 2.40, and the PI of the respective meta-analysis ranged from 0.56 to 2.11. Furthermore, 1 meta-analysis ( da Rosa et al 2018 ) assessed the efficacy of bioactive proteins for bone regeneration in implant-based rehabilitation. In this case, the first trial reported an estimate of –0.74 with the PI of the corresponding meta-analysis ranging from –0.61 to 0.07.…”
Section: Discussionmentioning
confidence: 99%
“…Dental implant placement is usually performed 6 months after MSFA to allow maturation of the grafted material, and transmucosal abutment connections and applications of functional loading are performed after an additional healing period of 4-8 months after implant placement [15,[27][28][29][30]. To improve bone regeneration and shorten the long treatment timeline from MSFA to completion of prosthetic rehabilitation, the effects of various bioactive proteins have been investigated [22,[31][32][33][34]. Platelet-rich fibrin (PRF), an autologous source of platelet derived growth factor, TGF-β, and VEGF, allowed early implant placement and accelerated bone healing with stable maintenance of graft volume [35,36].…”
Section: Plos Onementioning
confidence: 99%